The Effect of Salt Marsh on Residential Property Values. Issue 6 (2nd November 2021) - Gardner, George
Abstract: Salt marshes provide a myriad of critical ecosystem services yet have been threatened by urban expansion, sea level rise, and the armoring of coastal property. This study uses a hedonic property price method to evaluate the effects of salt marshes on residential property values in the Eastern Shore of Virginia. Contrary to findings from the wetland literature, results show an insignificant relationship between proximity to salt marsh and residential property values. In contrast, results show a statistically significant increase in property values with increasing proportions of salt marsh within 250 to 500 meters of the parcel. Furthermore, the increase in value is found to be larger for proportions of preserved relative to non-preserved salt marsh in this proximity of the home. The findings of this study can contribute to understanding the spatial patterns for housing premiums stemming from salt marshes. The information can be used to guide coastal management agencies on how to conserve salt marshes in a way that promotes residential property values.